Investigation of Employees' Job Satisfaction Determinants on the Services Realization - Pratiwi, Ratih; Febrian, Wenny Desty; Dharmawan, Donny; Judijanto, Loso; Setiawan, Roy (Universitas Padjadjaran, 2024)
The purpose of the research was to investigate the effects of workplace amenities, communication, discipline, and motivation on the job satisfaction of employees of PT. Aneka Infokom Tekindo Jakarta. The population sample of this study consisted of PT. Aneka Infokom Tekindo Jakarta's 92 personnel. The sampling method used was a census methodology, and the analytical instrument was multiple linear regressions. The results of the study indicated that work facilities, communication, work discipline, and work motivation all positively and significantly affected employees' job satisfaction at PT. Aneka Infokom Tekindo Jakarta, both partially and simultaneously.